Construction Occupational Safety and Health Expert Training at the Department of Public Works and Spatial Planning of the North Sumatra Provincial Government. - Herlina Jamaluddin EL- Matury (INSTITUT KESEHATAN DELI HUSADA, 2026)
This community service activity was conducted in the form of Construction Occupational Safety and Health (OSH) Expert Training aimed at enhancing the competencies of construction service personnel. The construction sector has a high rate of occupational accidents due to the complexity of technology, work methods, and the involvement of multiple disciplines and human resources. Although comprehensive Construction OSH regulations are in place, their effective implementation in the field still requires strengthened human resource capacity. The training program was delivered over a period of seven days using lectures, group discussions, case studies, and simulations of OSH document preparation. Evaluation was carried out through participatory observation, assignment assessments, and readiness for competency certification examinations for the positions of Junior Road Engineer, Junior Water Resources Engineer, and Junior Construction OSH Expert. The results indicate an improvement in participants’ understanding of OSH regulations, their ability to identify potential hazards, develop construction OSH programs, and prepare supervision reports. This activity contributes to strengthening the capacity of human resources in the construction services sector in accordance with the Indonesian National Work Competency Standards (SKKNI) and supports the implementation of the Construction Safety Management System (SMKK).